Emergence of Ferroelectricity in Halide Perovskites. Issue 8 (11th May 2020) - Shahrokhi, Shamim; Gao, Wenxiu; Wang, Yutao; Anandan, Pradeep Raja; Rahaman, Md Zahidur; Singh, Simrjit; Wang, Danyang; Cazorla, Claudio; Yuan, Guoliang; Liu, Jun‐Ming; Wu, Tom
Abstract: Perovskite oxides such as PbZr x Ti1− x O3 (PZT) and BaTiO3 show excellent dielectric, piezoelectric, pyroelectric, and ferroelectric properties simultaneously and have been widely used in capacitor, sensor, actuator, motor, surface acoustic wave devices, and energy storage applications. Recently, a variety of solution‐processed halide perovskite materials have been discovered to exhibit fascinating properties such as high charge mobility, strong light absorption, and even ferroelectricity. In this review, the recent progress on two classes of halide perovskite ferroelectrics is summarized. The first class is organo‐lead halide perovskite semiconductor such as MAPbI3 (MA=CH3 NH3 + ), which is intensively pursued for solar cell and light emitting diode applications. Dynamic ferroelectric polarization is believed to be one of the essential factors to protect carriers from being scattered by charged defects in these halide perovskites. The second class is normal/multilayered halide perovskite ferroelectrics with large polarization or strong piezoelectricity. The piezoelectric coefficient of these latter perovskites can be as high as ≈1540 pC N −1, comparable to those of PZT‐based ferroelectrics. Multiaxial polarizations and morphotropic phase boundaries are also demonstrated in such halide perovskites. Overall, the fast development of halide perovskite ferroelectrics opens a new avenue for not only advancing fundamental materials science but also designing novel electronic and photoelectric devices. Abstract : The recent progress on two classes of halide perovskite ferroelectrics are reviewed and compared, including organo‐lead halide perovskite semiconductors with extraordinary optoelectronic properties and halide perovskite insulators with polarization or strong piezoelectricity. The emergence of halide perovskite ferroelectrics opens a new venue for not only advancing fundamental materials science but also designing novel multi‐functional optoelectronic devices.